P121 A review of the telephone advice service for central and north west london integrated sexual health services. (18th May 2015) - Flavell, Sophie; Gillon, Chloe; Molloy, Sophie; Curran, Breda; Mercey, Danielle; D'Souza, Rachel; Jungmann, Eva
Abstract : Background/introduction: Although not advertised patients can phone our integrated sexual health services for advice and receive a call-back within 24 h. This service takes up significant resources without being funded. Aim(s)/objectives: Review the reasons for advice calls and establish their outcomes. Methods: A notes review was conducted of 50 calls received at each of the 3 main clinical sites in Central London over a 2 week period in July 2014. Data was collected regarding the reason for the phone call, call outcome and attendance within 6 weeks following the call. Results: The majority 129/150(86%) of calls were from existing patients. The majority of phone advice was related to contraception n = 44/160(28%), advice on sexually transmitted infections n = 22/160(14%) and patients with symptoms n = 31/160(19%). 24/44(66%) of the contraception calls were for intrauterine device (IUD) advice (pre-and post-insertion). 50/150(33%) patients were advised to attend the clinic of whom 39/50(78%) did attend. 66/150(44%) patients were given reassurance of whom 12/66(18%) attended anyway related to their call. Discussion: The phone advice service was largely used by existing users and almost 40% attended the service after the phone call. To make more effective use of resources we have designed frequently answered questions (FAQ) page on our website to address the most commonly asked questions. Phone advice is now only available to patients on post-exposure prophylaxis (PEP) and post-procedure eg. IUD insertion.